Dampak Trauma Kekerasan dalam Rumah Tangga Terhadap Perkembangan Psikis Anak - Isyatul Mardiyati (PSGA LP2M IAIN Pontianak, 2015)
Domestic Violence can happen to anyone, even though the family is considered as the best place for children's development. Some reports indicate that children in the family, often the victims of violence perpetrated by family members either directly or indirectly. Whereas the effects of this violence have the possibility of the same in the form of psychological trauma for children and eventually lead them to have a false perception of the violence, and assume that violence is one right way to resolve the issue. The experience of watching, hearing, even experienced violence in the family will no doubt lead to negative effects on the psychological of children. There are among children who experienced violence as a child, suffered prolonged trauma and lead to behavioral depression. But there are also some cases that actually show that children who have experienced violence in the past would later become perpetrators of the same crime as the first ever experienced. Not only short- term treatment should be the primary focus of handling trauma cases occurring in children. But should also be pursued in the long-term handling of recovery of post-traumatic stress disorder on children who have been traumatized. So, while reviving confidence in children, the support of families and civils become very important in creating a healthy environment for the child that lives in the present and future.